A Concise Review on Porous Adsorbents for Benzene and Other Volatile Organic Compounds - Jerzy Choma; Barbara Szczęśniak; Adam Kapusta; Mietek Jaroniec (Molecules)
Emissions of volatile organic compounds (VOCs) such as benzene, toluene, xylene, styrene, hexane, tetrachloroethylene, acetone, acetaldehyde, formaldehyde, isopropanol, etc., increase dramatically with accelerated industrialization and economic growth. Most VOCs cause serious environmental pollution and threaten human health due to their toxic and carcinogenic nature. Adsorption on porous materials is considered one of the most promising technologies for VOC removal due to its cost-effectiveness, operational flexibility, and low energy consumption. This review aims to provide a comprehensive understanding of VOC adsorption on various porous adsorbents and indicate future research directions in this field. It is focused on (i) the molecular characterization of structures, polarity, and boiling points of VOCs, (ii) the adsorption mechanisms and adsorption interactions in the physical, chemical, and competitive adsorption of VOCs on adsorbents, and (iii) the favorable characteristics of materials for VOCs adsorption. Porous adsorbents that would play an important role in the removal of benzene and other VOCs are presented in detail, including carbon-based materials (activated carbons, active carbon fibers, ordered mesoporous carbons, and graphene-based materials), metal-organic frameworks, covalent organic frameworks, zeolites, and siliceous adsorbents. Finally, the challenges and prospects related to the removal of VOCs via adsorption are pointed out.